The Pre-Tenure Years: Survive, Succeed, and Thrive. Issue 2 (2nd April 2016) - Merlo, Alida V.
Abstract : Pre-tenure faculty members often find it stressful and difficult to determine the best path to academic success in their new institution. This article offers an assessment, advice, and a perspective on the early stages of an academic career. Although there are variations in the types of institutions, programs, and departments, there are also similarities. Academic administrators and colleagues may be somewhat vague in their description of the expectations that they have for new hires. Nonetheless, engaging in research and publishing, good teaching, and relevant service are important. While sensitivity to the environment can help junior faculty develop an appropriate strategy, a commitment to research is essential.